Relationship Between Estradiol Levels Measured on the Initiation Day of GnRH Antagonist Treatment and Pregnancy Outcomes in Patients Receiving the Antagonist Protocol - Pınar Karaçin; Runa Özelçi; Enes Kumcu; Dilek Kaya Kaplanoğlu; Serdar Dilbaz; Yaprak Üstün (Medicina)
Background and Objectives: The aim of this study is to evaluate the relationship between serum estradiol (E2) levels measured on the day of antagonist administration and live birth rates (LBRs) in women undergoing IVF-ET with an antagonist protocol. Materials and Methods: Data from women who underwent IVF-ET with an antagonist protocol between 2011 and 2023 were retrospectively analyzed. Patients were divided into five groups on the basis of serum E2 levels measured on the day of antagonist administration (Group I: E2 < 400 pg/mL, Group II: 400 ≤ E2 < 650 pg/mL, Group III: 650 ≤ E2 < 800 pg/mL, Group IV:800 ≤ E2 < 1000 pg/mL, and Group V: E2 ≥ 1000 pg/mL). The independent effect of serum E2 levels on live birth was analyzed via an adjusted regression model. Results: A total of 1613 patients were included in the study. The overall LBR was 32.1%. The LBRs for Groups I, II, III, IV, and V were 28.9%, 37.8%, 26.4%, 32.2%, and 34.1%, respectively (p = 0.017). In the adjusted regression model, serum E2 levels measured on the day of antagonist administration < 400 pg/mL (OR: 0.752, 95% CI: 0.580–0.999, p = 0.048) and 650 ≤ E2 < 800 pg/mL (OR: 0.595, 95% CI: 0.388–0.911, p = 0.011) were identified as factors that reduce the likelihood of a live birth, adjusting for age, infertility duration, body mass index (BMI), cycle number, quality of embryo, and number of embryos transferred. Conclusions: The serum E2 level associated with the highest LBR in women undergoing IVF-ET with an antagonist protocol was found to be in the range of 400–650. Serum E2 levels < 400 pg/mL or in the range of 650–800 pg/mL were statistically significantly associated with a reduced LBR.